E EFEKTIVITAS ANALGETIK EKSTRAK BATANG PEPAYA (Carica papaya L.)PADA MENCIT JANTAN YANG DIINDUKSI LEMPENG PANAS - Sofia - Rahmi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Papaya stems (Carica papaya L.) are experimentally utilized by the community as new vegetables. Dried papaya stems contain auxiliary metabolites of flavonoids, tannins, glycosides, polyphenols, steroids and triterpenoids. This compound acts as an antioxidant. The flavonoid compounds found in papaya stems act as analgesics. The point of this ponder was to look at the pain relieving impact of papaya stems on male rats initiated by warm plate. Making wounds on creatures by implies of warming plates made with a estimate of 1cm x 1cm. The hair on the mice's backs was shaved, a warming cushion was connected to the mice's backs for around 2 seconds until they come to the dermis and fundamental tissue, causing the skin to rankle and peel in a few places. Pain relieving perceptions in test creatures were given after acceptance by regulating CMC-Na, paracetamol, papaya stem ethanol extricate at measurements of 100 mg/kgBW, 300 mg/kgBW and 600 mg/kgBW. Papaya stem extricate contains auxiliary metabolites of flavonoids, tannins and saponins that act as analgesics. At a measurements of 600 mg/kg body weight, the extricate had an pain relieving impact comparable to that of paracetamol.